2017
DOI: 10.1089/neu.2016.4507
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Effects of Morphine after Spinal Cord Injury

Abstract: Opioids and non-steroidal anti-inflammatory drugs are used commonly to manage pain in the early phase of spinal cord injury (SCI). Despite its analgesic efficacy, however, our studies suggest that intrathecal morphine undermines locomotor recovery and increases lesion size in a rodent model of SCI. Similarly, intravenous (IV) morphine attenuates locomotor recovery. The current study explores whether IV morphine also increases lesion size after a spinal contusion (T12) injury and quantifies the cell types that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 90 publications
0
27
0
Order By: Relevance
“…We herein showed that AST treatment significantly attenuates neural loss and demyelination at the lesion centre. It has been indicated that SCI‐induced histopathological damage is not restricted to the site of traumatic injury and extends both rostrally and caudally from the epicentre (Hook et al., ). Accordingly, in another study we showed that AST treatment protects spinal cord tissue at the rostral and caudal parts of clip compression injury, as well (Fakhri et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We herein showed that AST treatment significantly attenuates neural loss and demyelination at the lesion centre. It has been indicated that SCI‐induced histopathological damage is not restricted to the site of traumatic injury and extends both rostrally and caudally from the epicentre (Hook et al., ). Accordingly, in another study we showed that AST treatment protects spinal cord tissue at the rostral and caudal parts of clip compression injury, as well (Fakhri et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…5,6,8,9 Detrimental effects were also observed for some medications, including opioids, which attenuated the recovery of locomotor function and exacerbated pathophysiological processes in rodent models of spinal cord injury. 28,29 A detrimental opioid effect is in line with beneficial effects of naloxone (i.e., opioid antagonist), [30][31][32] and is highly concerning in light of the fact that opioids are ubiquitously administered for pain management in the early stages of injury (to > 80% of the patients). While completely removing or restricting opioids would be highly problematic and present with serious ethical concerns (i.e., weighing the management of acute pain with long-term neurological effects), opioids were among medications commonly administered to prevent the onset of pain.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, rats with SCI showed a substantial deficit in hindlimb movement at 1 dpi, and the rats recovered frequent stepping by the chronic 42 dpi time point. Locomotor recovery had not previously been assessed in this model (a T8 150 kdyn contusion with 1 s dwell; Putatunda et al, 2014; Gaudet et al, 2017; Hook et al, 2017). Interestingly, the post-SCI locomotor recovery presented here complements the findings of others: our average BBB score of 10.6 in female 42 dpi rats supports that this injury severity is between the severities reported previously (vs 150 and 200 kdyn with 0 s dwell; Scheff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%